What's the middle ground? Institutionalized vs. emerging water-related stakeholder engagement processes. Issue 3 (4th May 2019) - Hassenforder, Emeline; Clavreul, Delphine; Akhmouch, Aziza; Ferrand, Nils
Abstract: In this day and age, it is widely argued that stakeholder engagement in water-related decision-making processes yields many benefits, including legitimacy, acceptance and trust. Key legal frameworks, such as the European Water Framework Directive and the Aarhus Convention, have spurred the emergence of formal forms of stakeholder engagement. On the other hand, many engagement processes are spontaneous and self-organized. This article investigates the strategies used in formal (government-led) and informal (bottom-up) engagement processes in search of a middle ground. To this end, case studies in the Netherlands, the United States, Uganda and Ethiopia are analyzed using the OECD's stakeholder engagement checklist. We conclude with reflection on the ways forward to make formal and informal stakeholder engagement complementary.